Change in Spinal Alignment after Total Hip Arthroplasty - Radcliff, Kristen E (Orthop Surg, 2013)
OBJECTIVE: The study hypotheses were that: (i) there would be a difference in sagittal plane alignment between patients with symptomatic osteoarthritis of the hip and those with lumbar degenerative disk disease; and (ii) that sagittal plane lumbar alignment would change following total hip arthroplasty (THA). METHODS: In this prospective study, a series of patients without back pain or lumbar complaints who were scheduled to undergo THA underwent lateral lumbar radiography prior to and nine months after elective THA. Radiographic measurements of lumbar alignment included sacral slope, lumbar lordosis, and L (1) axis S (1) distance (L (1) ASD). All measurements were performed on upright, standing, lateral radiographs. A control group of patients underwent serial radiography over the same period for evaluation of lumbar degenerative disease. The independent sample t‐test was used to compare the mean sacral slope, lumbar lordosis, and L(1) ASD in the THA and control groups. RESULTS: There were 12 patients in the THA group and 34 in the control group. Mean follow‐up was 9 months. Average age in the control group was 63 years and in the THA group 64.2 years. The sacral slope was greater in the THA group (mean, 23°) than in the lumbar patients (control group) and this difference was statistically significant (mean, 11°, P = 0.001). There were no statistically significant differences between THA and control patients in lumbar lordosis or L (1) ASD. Change before and after THA was measured. There were no statistically significant differences in assessed radiographic variables preoperatively versus postoperatively. CONCLUSION: There is no significant change in spinal alignment after unilateral THA. At baseline, patients with symptomatic spine complaints have less sacral slope than their hip arthroplasty counterparts.